Pengaruh Terapi Musik Klasik terhadap Lama Persalinan Kala I Fase Aktif di Puskesmas Waode Buri Buton Utara - Masluroh, Masluroh; Asma, Nur (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Prolonged labor is one of the contributors to maternal mortality in the world, according to WHO, there are cases of prolonged labor in women in the world, namely 289 per 100,000 live births. Meanwhile, in Indonesia, the incidence of prolonged labor is the highest in ASEAN, namely 359 per 100,000 live births, mothers die due to prolonged labor. Music therapy can be a solution to reduce worry/anxiety, music can reduce pain, stress, anxiety and lower blood pressure. Reducing anxiety in mothers giving birth can reduce the muscles in labor so that they don't tense up so that the first stage can be accelerated and the labor process can run smoothly. To determine the effect of classical music therapy on the length of labor in the active phase of the first stage.Quasy experiment with a posttest group design. who has a control group. The sample in this study was all mothers giving birth with normal deliveries at the Waode Buri Community Health Center, North Buton in April - June 2024, totaling 30 people, the sampling technique was total sampling. The frequency distribution of the duration of the first stage of the active phase in mothers giving birth in the intervention group was mostly fast (86.7%) and in the control group the majority was in the slow category (40.0%). There is an effect of classical music therapy on the length of labor in the active phase of the first stage (p. value 0.000). There is an influence of classical music therapy on the length of labor during the first active phase at the Waode Buri Buton North Community Health Center. It is hoped that midwives will improve their delivery services by using music therapy to speed up the first stage so that the birthing process runs smoothly. Keywords: Childbirth, Classical Music Therapy  ABSTRAK Persalinan lama salah satu penyumbang kematian ibu di dunia, berdasarkan WHO terjadi kasus partus lama pada wanita di dunia yaitu 289 per 100.000 kelahiran hidup. Sementara di Indonesia terjadi kejadian partus lama menduduki urutan tertinggi di ASEAN yaitu 359 per 100.000 kelahiran hidup ibu meninggal akibat partus lama. Terapi musik dapat menjadi solusi untuk mengurangi kekhawatiran/kecemasan, musik bisa mengurangi rasa sakit, stres, kecemasan maupun menurunkan tekanan darah. Berkurangnya kecemasan pada ibu bersalin bisa mengurangi otot-otot persalinan agar tidak tegang sehingga dapat mempercepat kala satu dan proses persalinan berjalan dengan lancar. Mengetahui pengaruh terapi musik klasik terhadap lama persalinan kala I fase aktif. Quasy eksperiment dengan rancangan posttest group design. yang memiliki control group. Sampel dalam penelitian ini adalah seluruh ibu bersalin dengan persalinan normal di Puskesmas Waode buri, Buton Utara pada bulan April - Juni 2024 sebanyak 30 orang, teknik pengambilan sampel adalah total sampling. Distribusi frekuensi lama kala I fase aktif pada ibu bersalin  pada kelompok intervensi mayoritas cepat (86,7%) dan pada kelompok kontrol mayoritas dengan kategori lambat (40,0%). Ada pengaruh terapi musik klasik terhadap lama persalinan kala I fase aktif (p. value 0,000). Ada pengaruh terapi musik klasik terhadap lama persalinan kala I fase aktif di Puskesmas Waode Buri Buton Utara. Diharapkan bidan dalam meningkatkan pelayanan ibu bersalin menggunakan terapi musik agar dapat mempercepat kala I  sehingga proses persalinan berjalan dengan lancar.                                                                                    Kata Kunci: Persalinan, Terapi musik klasik